The Content of US Plastic Surgery Private Practices' Websites. Issue 5 (June 2021) - Ananthasekar, Shivani; Patel, Jason J.; Patel, Neha J.; Awad, Shadi K.; Boyd, Carter J.; King, Timothy W.
Abstract : Introduction: Connecting patients with healthcare providers continues to grow as the digital era evolves. A successful website has the power to influence patients on choosing a practice and provider. The objectives of this study were to characterize information provided on private practice websites of plastics surgeons in the United States and to assess the relationship among the websites based on the number of years that the physicians have been in practice. Methods: Newly board-certified plastic surgeons by the American Board of Plastic Surgery in 2005, 2010, and 2015 were identified. A Google search was conducted on all participants, and only those in private practice were included in this study. Each webpage was quantitatively and qualitatively assessed for the presence or absence of 23 criteria that were categorized as practice, physician, patient, or procedure information. χ 2 was used for statistical analysis using Microsoft Excel (PSPP 1.2.0). A P value of less than 0.05 was considered statistically significant. Results: Most plastic surgeons in each cohort were currently in private practice. A total of 532 plastic surgery private practice websites were analyzed. The data points found on 100% of the websites were directions to the facility and the contact for any billing questions. Most websites provided information on the practice and its surgeons. The most common web-based data points included online consultations and links to their social media. Information on expenses incurred by patients, such as cancellation policies and consultation fees, was least commonly listed. Conclusions: Our study shows that the number of years in practice is not associated with comprehensiveness of their website's content. This study provides insight into the content of plastic surgery private practices' websites in the United States in relation to the practice, the physician, the patient, and the procedures. This information may be useful for expanding and optimizing their websites. This has the potential to increase patient satisfaction and visibility of the practice. The success of these businesses is vital as the private sector in plastic surgery continues to grow.